Penerapan Pendekatan Andragogi dalam Meningkatkan Partisipasi Belajar Peserta Didik Program Kesetaraan Paket C di SKB Negeri Surabaya - Nur Rahma Madia Putri; I Ketut Atmaja Jhony Artha (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
This research is motivated by the low learning participation of students at the Surabaya State SKB. Students are adults who need an andragogy approach in implementing learning.The goal to be achieved in this study is to examine the application of the andragogical approach in increasing the learning participation of Equivalence Package C students at the SKB Negeri Surabaya. This study uses a qualitative approach and descriptive research type. Data collection techniques used are in-depth interview techniques, participant observation, and documentation. The results of this research are the application of andragogy in increasing student learning participation. given in the form of an e-module so that it is difficult for students to understand the learning material.